2015
DOI: 10.1016/j.bbamem.2014.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of an atomic model for bacterial TSPO from electron microscopy density, evolutionary constraints, and biochemical and biophysical data

Abstract: The 18 kDa protein TSPO is a highly conserved transmembrane protein found in bacteria, yeast, animals and plants. TSPO is involved in a wide range of physiological functions, among which the transport of several molecules. The atomic structure of monomeric ligand-bound mouse TSPO in detergent has been published recently. A previously published low-resolution structure of Rhodobacter sphaeroides TSPO, obtained from tubular crystals with lipids and observed in cryo-electron microscopy, revealed an oligomeric str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Because of the high affinity of the cholesterol-TSPO interaction, an additional, currently unknown, mechanism would then be required to release cholesterol. Potential subsequent transport/translocation of cholesterol might occur at a TSPO oligomerization interface [35,36,38,44,45], in agreement with the ability of TSPO to form polymers in vivo [46].…”
Section: Tspo-cholesterol Interactions and Translocationsupporting
confidence: 54%
“…Because of the high affinity of the cholesterol-TSPO interaction, an additional, currently unknown, mechanism would then be required to release cholesterol. Potential subsequent transport/translocation of cholesterol might occur at a TSPO oligomerization interface [35,36,38,44,45], in agreement with the ability of TSPO to form polymers in vivo [46].…”
Section: Tspo-cholesterol Interactions and Translocationsupporting
confidence: 54%
“…Because TM helix 1 is the least conserved of the five TM regions and is more polar in RsTspO than in mTSPO/PBR, where the functional unit is a monomer, we suggested that TM helix 1 is involved in the dimer interface of RsTspO [22]. However, alternative models were also proposed [31,32].…”
Section: Structural Properties Of Tspo/pbrmentioning
confidence: 80%
“…This method would have helped resolve the L6 loop of the β-barrel protein FhaC in the original crystal structure [74,75], as explained above. In a different study the mitochondrial translocator protein TSPO dimer structure was disputed based on differences in data from NMR [126], EM of helical crystals [127], Rosetta modeling [128], and sequence coevolution analysis [40,129]. A high resolution lipidic cubic phase crystal structure finally resolved the structure of the TSPO dimer [130], which had the topology predicted from sequence coevolution analysis.…”
Section: Integrative Modeling Of Membrane Protein Structurementioning
confidence: 99%